Institutional Response to Implement 4IR Competencies into Programme Offerings of Technical and Vocational Education and Training in Indo-Pacific - Wickramasinghe, G.L.D.; Wickramasinghe, Vathsala (Journal of Technical Education and Training, 2024)
The paper provides results of a study that investigated the response of technical and vocational education and training (TVET) institutions for the implementation of 4th industrial revolution (4IR) competencies into programme offerings. The investigation was confined to TVET in science, technology, engineering, and mathematics (STEM) fields at the tertiary level. 470 TVET staff responded to the survey from 15 countries, all of which belonging to the middle-income category in Indo-Pacific. The study examined institutional response covering eight areas, i.e., financial support for digital transformations, support for partnerships, job market sensitivity, support for changes to programme offerings, popularization of programme offerings, support for teacher development, support for adherence to quality, and the overall assessment of institution management in response to implementing 4IR competencies into programme offerings. The results showed significant differences in the institutional response for the eight areas by the institution type - TVET regulatory bodies, TVET teacher training and research institutes, TVET universities, polytechnics, and TVET colleges.